Komparasi Contextual Learning dan Experiental Learning dalam Proses Pembelajaran - Aprilia Sari Yudha (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
For good teaching, teachers need to understand the various learning strategies available so they can sort out the most suitable strategy for teaching a particular subject in a powerful and easy way. Therefore, a teacher must carefully consider the learning strategy that will be used because it affects students' ability to master the material or achieve optimal learning achievement, one example of a learning strategy that is often used is contextual learning models and experiential learning. Contextual learning and experiential learning are both learning methods that emphasize direct experience in real situations. Contextual learning places subject matter in the context of everyday life, while experiential learning requires students to learn through action and reflection on their experiences. Both of these methods have the potential to increase students' understanding, motivation, and skills in sustainable and relevant learning.